Multigenerational variation in the nutrients and digestion of western flower thrips (Frankliniella occidentalis) depends on the nutritive quality of different foods. Issue 2 (13th April 2023) - Yue, Wen Bo; Zhou, Dan; Li, Ding Yin; Zhi, Jun Rui; Fang, Xin Lei; Qiu, Xin Yue
Abstract: Western flower thrips (WFTs), Frankliniella occidentalis (Thysanoptera, Thripidae), is one of the most serious pests that attack rose flowers. Little is known about the effect of different parts of the rose flower on nutritional contents and digestive enzyme activities in thrips. This study assessed variations in the nutritional contents and digestive enzyme activities in the second-instar larvae and adults WFTs fed on 3 food types (rose petals, rose flowers, and honey solution + kidney bean pods) for multiple generations. The highest contents of soluble sugar (in 10% honey solution + kidney bean pods), amino acid (in rose flowers), and protein (in rose flowers) were observed, respectively. Soluble sugar and protein contents in the second-instar larvae and adults fed on rose petals decreased in the F1 generation but increased in the F2 generation and remained at higher levels until the F7 generation. Feeding of thrips with 3 food types increased the lipid content in the F1 generation, which peaked in the F2 generation and remained high until the F7 generation. In most cases, α-amylase and trypsin activities significantly decreased in the F1 generation after feeding on rose petals and then prominently increased in the F2 generation. In contrast, chymotrypsin activity remarkably increased and peaked in the F1 generation after second-instar larvae thrips fed on rose petals. There were correlations among the contents of 3 nutrient related positively with the activities of α-amylase and trypsin in WFTs second-instar larvae and adults, respectively. Overall, variations in the nutrient properties of the 3 food types caused changes in nutrient contents and digestive enzyme activities in thrips.